2010
DOI: 10.1097/eja.0b013e328338883c
|View full text |Cite
|
Sign up to set email alerts
|

A simplified risk score to predict difficult intubation: development and prospective evaluation in 3763 patients

Abstract: The new simplified multivariate risk score for difficult intubation may prove to be useful in clinical practice for predicting a difficult airway. Presence of upper front teeth, a history of difficult intubation, any Mallampati status different from '1' and equal to '4' and mouth opening less than 4 cm are independent risk factors for difficult endotracheal intubation. With each of these risk factors, the likelihood increases from 0 (when no risk factor is present) to 17% (when four or five factors are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…However, logistic regression showed that an increase in one unit means that the likelihood of difficult intubation is 1.27 times higher. In most cases, greater neck circumference is associated with high body weight and some scoring models include weight as a risk factor for difficult intubation 8,[13][14][15] . We did not confirm that.…”
Section: Discussionmentioning
confidence: 99%
“…However, logistic regression showed that an increase in one unit means that the likelihood of difficult intubation is 1.27 times higher. In most cases, greater neck circumference is associated with high body weight and some scoring models include weight as a risk factor for difficult intubation 8,[13][14][15] . We did not confirm that.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthesia literature has demonstrated factors associated with difficult intubation (eg, obesity and short thyromental distance) [14][15][16][17]. By contrast, in the ED setting, the evidence to predict difficult airways remains scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies 12,14,26,35 indicated that limited mouth opening is strongly associated with difficult intubation as observed by us. If IIG <3 cm is taken, then it becomes highly sensitive test (100%) for prediction of difficult intubation.…”
Section: Discussionmentioning
confidence: 95%